Linking inter-individual differences in the perceptual load effect to spontaneous brain activity - Liu, Lu; Tan, Jinfeng; Chen, Antao (Frontiers in Human Neuroscience, 2015)
Previous researches have widely demonstrated that the interference from peripheral distractor will decrease when the task load is high. However, no study to date has paid attention to the individual differences in perceptual load effect and little is known of spontaneous brain activity associated with perceptual load effect during resting state. To investigate this issue, we used resting-state fMRI to examine the relationship between the amplitude of low-frequency fluctuations (ALFFs) and perceptual load effect (PLE). The results showed that there were large individual differences in PLE and we found PLE was significantly associated with ALFFs in left inferior temporal gyrus (ITG) and left precentral/postcentral gyrus. The present study suggested that the PLE was measurable, and there were individual differences in this effect. Moreover, these results implicated that capacity limitation and competitive interaction involved in visual attention and response control may contribute to the modulation induced by perceptual load.